3D Printing of Interdigitated Dielectric Elastomer Actuators. (11th November 2019) - Chortos, Alex; Hajiesmaili, Ehsan; Morales, Javier; Clarke, David R.; Lewis, Jennifer A.
Abstract: Dielectric elastomer actuators (DEAs) are soft electromechanical devices that exhibit large energy densities and fast actuation rates. They are typically produced by planar methods and, thus, expand in‐plane when actuated. Here, reported is a method for fabricating 3D interdigitated DEAs that exhibit in‐plane contractile actuation modes. First, a conductive elastomer ink is created with the desired rheology needed for printing high‐fidelity, interdigitated electrodes. Upon curing, the electrodes are then encapsulated in a self‐healing dielectric matrix composed of a plasticized, chemically crosslinked polyurethane acrylate. 3D DEA devices are fabricated with tunable mechanical properties that exhibit breakdown fields of 25 V µm −1 and actuation strains of up to 9%. As exemplars, printed are prestrain‐free rotational actuators and multi‐voxel DEAs with orthogonal actuation directions in large‐area, out‐of‐plane motifs. Abstract : 3D dielectric elastomer actuators (DEAs) have been printed that exhibit in‐plane contraction. Several DEA devices consisting of interdigitated vertical electrodes infilled with dielectric matrices are fabricated and characterized, including voxelated devices that actuate in orthogonal directions and prestrain‐free rotational actuators.